Asuransi Sebagai Jaminan Hak Anak Dan Perlindungannya Dari Kekerasan Ekonomi - Anisatul Latifah; Arif Sugitanata; Siti Khamidatus Sholikhah (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Insurance is one of the financial institutions that provides guarantees to its customers for the losses they get or the guarantee of future funds after making an agreement contract, in the context of a family, children have rights that must be fulfilled as a mandate from God. Therefore, this study explains how insurance as a guarantee of children's rights and their protection from economic violence. By utilizing literature studies whose primary data sources come from books, journals and books of law related to the studies conducted, where the data is processed descriptively-analytically so as to be able to explain and describe the purpose of the research objectives carried out. The results of this study indicate that with the certainty of guarantee with the contract that has been agreed with the insurance company, the rights of children are more guaranteed to be carried out by parents in a situation even though they have died or after their parents retire from work. Although not achieved less than the maximum, the achievement of children's rights at least financial needs can be implemented with reasonable standards, not not implemented at all. OJK is an institution appointed by law as the party responsible for protecting the insured. The form of this responsibility is to receive complaints, resolve insurance business disputes and facilitate the settlement of insurance claim disputes in accordance with the agreement of the parties.